Traditional healing practice and folk medicines used by Mishing community of North East India - Shankar, Rama (Medknow Publications & Media Pvt Ltd, 2012)
Assam and Arunachal Pradesh have very rich tradition of herbal medicines used in the treatment of various ailments. Tribal communities practice different types of traditional healing practices. Enough documentation is available on the healing practices in other tribal communities except Mishing community of Assam and foot hill of East Siang district of Arunachal Pradesh hence the attempt was made for the same. A survey on folk medicinal plants and folk healers of Mishing tribe was conducted in few places of Lakhimpur and Dhemaji district of Assam and East Siang district of Arunachal Pradesh, where this ethnic group is living since time immemorial. All information was collected based on interview and field studies with local healers within the community. The identification of medicinal plants collected with help of indigenous healers was done. Such medicines have been shown to have significant healing power, either in their natural state or as the source of new products processed by them. This study is mainly concentrated with plants used to cure diseases and to enquire about different healing systems. Detail note on the method of preparation of precise dose, the part/parts of plants used and method of application is given.